Pediatric Medical Emergencies and Injury Prevention Practices in the Pediatric Emergency Unit of Kenyatta National Hospital, Nairobi, Kenya. Issue 1 (21st January 2021) - Myers, Justin G.; Nwakibu, Uzoma A.; Hunold, Katherine M.; Wangara, Ali Akida; Kiruja, Jason; Mutiso, Vincent; Thompson, Peyton; Aluisio, Adam R.; Maingi, Alice; Dunlop, Stephen J.; Martin, Ian B.K.
Abstract : Introduction: The epidemiology and presence of pediatric medical emergencies and injury prevention practices in Kenya and resource-limited settings are not well understood. This is a barrier to planning and providing quality emergency care within the local health systems. We performed a prospective, cross-sectional study to describe the epidemiology of case encounters to the pediatric emergency unit (PEU) at Kenyatta National Hospital in Nairobi, Kenya; and to explore injury prevention measures used in the population. Methods: Patients were enrolled prospectively using systematic sampling over four weeks in the Kenyatta National Hospital PEU. Demographic data, PEU visit data and lifestyle practices associated with pediatric injury prevention were collected directly from patients or guardians and through chart review. Data were analyzed with descriptive statistics with stratification based on pediatric age groups. Results: Of the 332 patients included, the majority were female (56%) and 76% were under 5 years of age. The most common presenting complaints were cough (40%) fever (34%), and nausea/vomiting (19%). The most common PEU diagnoses were upper respiratory tract infections (27%), gastroenteritis (11%), and pneumonia (8%). The majority of patients (77%) were discharged from the PEU, while 22% were admitted. Regarding injury prevention practices, the majority (68%) of guardians reported their child never used seatbelts or car seats. Of 68 patients that rode bicycles/motorbikes, one reported helmet use. More than half of caregivers cook at potentially dangerous heights; 59% use ground/low level stoves. Conclusions: Chief complaints and diagnoses in the PEU population were congruent with communicable disease burdens seen globally. Measures for primary injury prevention were reported as rarely used in the sample studied. The epidemiology described by this study provides a framework for improving public health education and provider training in resource-limited settings.